(untitled) (Journal of Energy and Safety Technology (JEST), 2023)
A study on profiling of ammonia concentration and its validation using two types of direct reading instruments has been conducted for eight months from September 2021 till May 2022 in four different zones in West Malaysia. The study is using a high performance multigas analyzer integrated with Fourier Transform Infrared (FTIR) and Multirae data analyzer to measure ammonia concentration in thirty-eight ice-production facilities in Malaysia. This study is limited to databases of ice-production facilities registered with the Department of Occupational Safety and Health (DOSH) Malaysia. The study involves thirty-eight ice-production facilities with fourteen compliance verification using USECHH checklist. The results of monitoring and validation confirmed that ammonia is detected at various locations in the factory layout. It is found to be localized and concentrated at the machine room followed by machine room combined with production room. Both instruments seem to show similar trend which can validate the profile obtained for ammonia in the ice facilities. Recommendations are suggested for employers to improve layout of the ice-production facilities based on these measurements. The study also seeks to find a correlation between the compliance of these facilities with the Use and Standards of Exposure of Chemicals Hazardous to Health (USECHH) Regulations 2000 and compliance with ammonia checklist from the Guideline of Safe Management of Ammonia Refrigeration System 2020. Pre and post assessment is conducted using the same ammonia checklist to identify any gap. It was found that the results obtained for the USECHH compliance, ammonia checklist compliance either pre or post assessment are not positively correlated. This finding emphasizes that there is still a lack of commitment from these ice-production facilities even after the visits by authorities. Comparison between the monitoring data and the degree of compliance using ammonia checklist from the said guideline was also made. The results obtained emphasize that there is no strong correlation between the monitoring data and the degree of compliance using the ammonia checklist. This study shows an insight of chemical management in Malaysia at ice-production facilities and provides suggestions, recommendations, measures and outcomes of enforcement. Future measures to be taken is also suggested to boost compliance. At the same time, the outcomes and implications of this study on chemical management and chemical safety status in Malaysia can also assist other developing countries to improve their chemical management. Future research with risk modelling of ammonia leakages could also be ventured into. Ice plants are recommended to redesign their layout based on this study. Keywords: ammonia profiling, compliance enforcement, ice production facilities, lack of commitment, USECHH compliance.